Gendered Relationship of Childbearing with Earnings Accumulated by Midlife in Two Nordic Countries - Nisén Jessica; Erlandsson Anni; Jalovaara Marika (Turun yliopisto, 2025)
Nordic countries are considered advanced in gender equality, but also in these countries women still take longer family leaves and have lower earnings than men. This study provides novel insight by assessing the differences in accumulated earnings by midlife associated with childbearing among women and men in Finland and Sweden. We place particular attention to the magnitude of gender gaps in accumulated earnings across groups. We hypothesize larger gender gaps among those with a larger number of children, among those with a lower level of education, and overall, in Finland. The study is based on full-population register data, with highly accurate measures of earnings across decades. Our results indicate that women born in 1974–1975 accumulated on average 32 % and 29 % less labor earnings than men by age 44 in Finland and Sweden, respectively. Childbearing strongly modifies the gender gap especially in Finland, and the highly educated have moderately smaller gaps in both countries.